Evaluasi Hubungan Kualitas Pelayanan Kesehatan Terhadap Kepuasan Pasien di Instalasi Rawat Jalan Rumah Sakit Umum Daerah Tarutung Tahun 2023 - Hutabarat, Andrian; Manurung, Kesaktian; Lina Tarigan, Frida; Nababan, Donal; Sipayung, Rosetty (Journal of Pharmaceutical and Sciences, 2025)
This study aims to evaluate the relationship between the quality of healthcare services and patient satisfaction at the Outpatient Installation of Tarutung Regional General Hospital in 2023. The research employed a cross-sectional design, focusing on five dimensions of service quality: tangible (facilities), reliability, responsiveness, assurance (quality assurance), and empathy. Data were collected through questionnaires administered to 96 outpatients from September 2023 to February 2024. The results indicate excellent overall service quality at the Outpatient Installation of Tarutung Regional General Hospital. However, certain dimensions require improvement, such as responsiveness (10.5% rated as poor), assurance (6.10%), tangible (6.30%), empathy (5.20%), and reliability (9.40%). While 72.9% of patients expressed satisfaction, 27.1% reported dissatisfaction. Statistical analysis revealed a significant relationship between healthcare service quality and patient satisfaction (p < 0.05). These findings underscore the importance of enhancing service quality, particularly in the underperforming dimensions, to improve patient satisfaction. This study provides practical contributions for hospital management in designing strategies to improve the quality of service.